2011
DOI: 10.5664/jcsm.1080
|View full text |Cite
|
Sign up to set email alerts
|

Compulsion or Chronobiology? A Case of Severe Obsessive-Compulsive Disorder Treated with Cognitive-Behavioral Therapy Augmented with Chronotherapy

Abstract: Objectives: Individuals with treatment-resistant obsessive compulsive disorder (OCD) have elevated rates of delayed sleep phase. This report describes a patient with severe OCD who had failed prior trials of pharmacotherapy and psychotherapy, and whose symptoms were associated with delayed bedtimes and delays in the time she initiated her nighttime compulsions. Methods: Case report. Results: A 54 year-old woman with OCD kept sleep/symptom logs as an adjunct to traditional cognitive-behavioral therapy for OCD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 6 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…As the relationship between eveningness and emotional dysregulation seems to be at least partly mediated by sleep complaints ( Levandovski et al., 2011 ; Rosenberg et al., 2014 ; Simor, Zavecz, et al., 2015 ), treatments focusing on circadian rhythms and sleep quality might be beneficial for patients with OCD. In fact, pharmacological and behavioral interventions aiming to normalize circadian rhythms showed promising outcomes in case studies of OCD patients ( Coles & Sharkey, 2011 ; Fornaro, 2011 ). Moreover, although chronotype is considered to be a relatively stable trait-like construct ( Klei et al., 2005 ), Hasler, Buysse, and Germain ( 2016 ) showed that a shift toward morningness during a behavioral sleep intervention resulted in improved affect, better sleep quality, and reduced depressive symptoms in a group of insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the relationship between eveningness and emotional dysregulation seems to be at least partly mediated by sleep complaints ( Levandovski et al., 2011 ; Rosenberg et al., 2014 ; Simor, Zavecz, et al., 2015 ), treatments focusing on circadian rhythms and sleep quality might be beneficial for patients with OCD. In fact, pharmacological and behavioral interventions aiming to normalize circadian rhythms showed promising outcomes in case studies of OCD patients ( Coles & Sharkey, 2011 ; Fornaro, 2011 ). Moreover, although chronotype is considered to be a relatively stable trait-like construct ( Klei et al., 2005 ), Hasler, Buysse, and Germain ( 2016 ) showed that a shift toward morningness during a behavioral sleep intervention resulted in improved affect, better sleep quality, and reduced depressive symptoms in a group of insomnia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, careful timing of medication dosing provides clinicians with a means to effectively treat hypertension-associated disease severity. Other disparate examples involve the optimization of chrono-based formulation for the treatment of rheumatoid arthritis using low doses of prednisone (clinical trial NCT00650078, [ 34 ]) as well as the development of chronopharmacotherapy adjunctive approaches to enhance cognitive-behavioral therapies for treating a resistant form of obsessive-compulsive disorders [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 One case study reported successful outcomes following a combination of agomelatine and behavioral interventions targeting circadian realignment. 32 The patient had long-standing religious and cleaning compulsions and did not respond to SSRIs and classical OCD-focused CBT. Initially, it was noted that she had a marked delay in her sleep-wake schedule, which was accompanied by fatigue, poor concentration, and worse difficulties inhibiting compulsions at nighttime.…”
Section: Behavioral Circadian Approachesmentioning
confidence: 99%
“…30 In addition, a few case reports highlighted increased compulsions late at night, with worse difficulties to dismiss intrusive thoughts and resist the urge to engage in behaviors with excessive perfectionism. 31,32 These daily rhythms in OC symptoms may possibly be potentiated by circadian variations in parallel symptoms, such as general anxiety, which has also been observed to worsen in the afternoon or evening. 33 OC symptoms have been proposed to relate to cognitive inhibition and working memory dysfunctions, 34 two components of executive functions which are sensitive to interactions between homeostatic and circadian processes.…”
Section: Cyclical Patterns Of Oc Symptomsmentioning
confidence: 99%
See 1 more Smart Citation